Evaluation of fundamental viscoelastic functions by a nonlinear viscoelastic model. Issue 12 (22nd February 2017) - Spathis, Gerasimos; Katsourinis, Stylianos; Kontou, Evagelia
Abstract : In this work, a new constitutive equation for the description of the nonlinear viscoelastic response of polymeric materials is presented, by proposing modifications on a model developed in previous works. This time‐dependent equation has been derived on the basis of transient model, and a new assumption regarding the kinetics of active molecular chains due to the imposed deformation. The present treatment was proved to be more flexible, given that it contains a relaxation function that has been derived by considering, instead of first‐order kinetics, a fractional derivative that controls the rate of molecular chain detachment from their junctions. It has been further explored that the potential of this equation to be employed for the evaluation of the dynamic modulus master curve, once the experimental data of the compliance modulus of a polymeric structure have been matched. POLYM. ENG. SCI., 57:1389–1395, 2017. © 2017 Society of Plastics Engineers